Pulpo-Periodontal Regeneration: Management of Partial Failure Revascularization - Said Dhaimy; Sara Dhoum; Hind Amarir; Hafsa El Merini; Sellama Nadifi; Amal El Ouazzani (Hindawi Limited, 2017)
The aim of this work is to present a case of management of an open apex on a lower molar by using tissue engineering, with two endodontic procedures in the same tooth. We had to resort to pulp regeneration on the distal root and apexification with MTA on the mesial roots after the failure of regenerative therapy on those ones. The management consisted in scheduling regular follow-ups combined with X-rays. After 24 months, the radiological control has shown pulpo-periodontal regeneration associated with walls thickening and distal root elongation and periapical ad integrum healing.